2015
DOI: 10.1073/pnas.1415836112
|View full text |Cite
|
Sign up to set email alerts
|

Linking fecal bacteria in rivers to landscape, geochemical, and hydrologic factors and sources at the basin scale

Abstract: Linking fecal indicator bacteria concentrations in large mixed-use watersheds back to diffuse human sources, such as septic systems, has met limited success. In this study, 64 rivers that drain 84% of Michigan's Lower Peninsula were sampled under baseflow conditions for Escherichia coli, Bacteroides thetaiotaomicron (a human source-tracking marker), landscape characteristics, and geochemical and hydrologic variables. E. coli and B. thetaiotaomicron were routinely detected in sampled rivers and an E. coli refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 65 publications
4
82
0
Order By: Relevance
“…Canal presence was not significantly associated with exceedance levels; however, when comparing rivers and canals together, their combined significance despite distance from sampling point suggests an association with FIB contributions. Rivers and canals have potential to carry significant amounts of FIB from runoff accumulating from the inland areas (Nevers et al 2007, Byappanahalli et al 2010, Vergougstraete et al 2015) This includes influences from agricultural and urban land-uses, both of which are associated with elevated FIB levels (Strauch et al 2014, Walters et al 2011). In addition to land use, studies have also shown that riverbank sediments carry and eventually release significant amounts of FIB from their banks (Desmarais et al 2002, Brinkmeyer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Canal presence was not significantly associated with exceedance levels; however, when comparing rivers and canals together, their combined significance despite distance from sampling point suggests an association with FIB contributions. Rivers and canals have potential to carry significant amounts of FIB from runoff accumulating from the inland areas (Nevers et al 2007, Byappanahalli et al 2010, Vergougstraete et al 2015) This includes influences from agricultural and urban land-uses, both of which are associated with elevated FIB levels (Strauch et al 2014, Walters et al 2011). In addition to land use, studies have also shown that riverbank sediments carry and eventually release significant amounts of FIB from their banks (Desmarais et al 2002, Brinkmeyer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the HF183 human marker in the upper branches of the Humber River could be two small wastewater treatment plants upstream of site R2, sewage cross-connects within storm water systems in smaller rural communities, or leaking septic systems. An MST study using the HF183 marker in Michigan in the United States recently detected widespread septic system impacts on surface water quality in rural areas (55). The increases in both E. coli and human marker concentrations in the middle and lower Humber River are likely due to increased impacts from combined sewer overflows and storm water systems with sewage cross-connections.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomics has been used to determine the influence of fluvial networks on the co-occurrence of microbes, by examining biofilms in over a hundred streams (Widder et al, 2014). The distribution and origins of fecal bacteria have been determined in large mixed-use watersheds in Michigan, USA, also using omics technologies (Verhougstraete, Martin, Kendall, Hyndman, & Rose, 2015). Similar ecosystem wide approaches have been used to demonstrate how below-ground microbial diversity might be a primary driver of plant diversity and productivity (Bardgett & Van Der Putten, 2014).…”
mentioning
confidence: 99%